Výuka kvantitativní analýzy dat jako součást metodologie výzkumu v pedagogických studijních programech veřejných vysokých škol v ČR - Ilona Kočvarová; Petr Soukup (Karolinum Press, 2019)
The empirical study presents a research survey in the field of teaching quantitative data analysis as a part of research methodology in educational study programs of public universities in the Czech Republic. The survey is based on content analysis of 231 study subjects' syllabuses, a census survey gained in 2017. Although the results are restricted to the designed curriculum and bundled with many limits, they point to the fact that quantitative analytical training of future educationalists is mostly general, non-conceptual, often unqualified and does not reflect current trends. In the time of (re)accreditation of educational study programs the authors call for adaptation of quantitative analytical training on the level of pedagogical practice as well as academic sphere. The paper aims to contribute to informing the educational community about the current state of teaching in the given field and to open a discussion that would lead to conceptual adjustments of current study programs.